1998
DOI: 10.2135/cropsci1998.0011183x003800050035x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Diverse Germplasm for Soybean Yield Improvement

Abstract: Introgression of diverse germplasm into the current soybean [Glycine max (L.) Merr.J genetic base may increase genetic variability and lead to greater gains from selection. The objective of this research was to evaluate the genetic diversity and agronomic performance of experimental lines derived from plant introductions (Pis) maintained in the USDA Soybean Germplasm Collection. These Pis are known to be genetically distinct from the ancestors of the modern North American soybean cultivars. Experimental lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…Among worldwide germplasm collections, there are an estimated 47,000 G. max accessions and 8500 G. soja accessions that could be evaluated for yield increasing genes (Carter et al, 2004). Even with these difficulties, researchers have been able to identify a number of valuable yield increasing alleles from exotic plant introductions (PIs) (Concibido et al, 2003;Guzman et al, 2007;Kabelka et al, 2004;Li et al, 2008;Smalley et al, 2004;Thompson and Nelson, 1998), providing evidence that mining germplasm may be beneficial to improving elite soybean yields. Yield is also often confounded with traits like maturity date or plant height, resulting in difficulty in separating genes that control these traits (Concibido et al, 2003;Kabelka et al, 2004;Reyna and Sneller, 2001;Specht et al, 2001;Thompson and Nelson, 1998;Wang et al, 2004).…”
Section: Confirmation Of a Seed Yield Qtl In Soybeanmentioning
confidence: 99%
“…Among worldwide germplasm collections, there are an estimated 47,000 G. max accessions and 8500 G. soja accessions that could be evaluated for yield increasing genes (Carter et al, 2004). Even with these difficulties, researchers have been able to identify a number of valuable yield increasing alleles from exotic plant introductions (PIs) (Concibido et al, 2003;Guzman et al, 2007;Kabelka et al, 2004;Li et al, 2008;Smalley et al, 2004;Thompson and Nelson, 1998), providing evidence that mining germplasm may be beneficial to improving elite soybean yields. Yield is also often confounded with traits like maturity date or plant height, resulting in difficulty in separating genes that control these traits (Concibido et al, 2003;Kabelka et al, 2004;Reyna and Sneller, 2001;Specht et al, 2001;Thompson and Nelson, 1998;Wang et al, 2004).…”
Section: Confirmation Of a Seed Yield Qtl In Soybeanmentioning
confidence: 99%
“…Such an insight could be achieved through molecular characterization of soybean germplasm using DNA markers, which are more informative, stable and reliable, as compared to conventional methods like pedigree analysis and morphological diversity. Early studies have shown utilization of molecular markers for identification of genetically diverse genotypes to use in crosses in breeding programme (Maughan et al 1996;Thompson and Nelson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, geographically different genetic resources of soybean are quite different genetically even though they are not completely different. A DNA marker study by Thompson and Nelson (1998) revealed that introgression of genetic diversity from exotic genetic resources can contribute to increasing the yield of current USA cultivars. Therefore it can also be expected that exchanging soybean genetic resources between Japan, China and Brazil would expand their genetic base and increase variability especially when Brazilian varieties are used for soybean breeding in Japan and China or when Chinese cultivars are used in breeding programs in Brazil.…”
mentioning
confidence: 99%